The Role of the Family Hope Program (PKH) in Improving the Economy of the Poor in Renggeang Village, Limboro District Polewali Mandar Regency - Arfa Aprilianti Arfa Aprilianti (Pustaka Digital Indonesia, 2022)
This study aims to (1) know the implementation of the family hope program in Renggeang Village, Limboro Subdistrict, Polewali Mandar Regency (2) and to know the improvement of the family hope program in improving the economy of the poor in Renggeang Village, Limboro District, Polewali Mandar Regency. The type of research used in this study is descriptive qualitative research. The population in this study was 121 people. Meanwhile, a sample of 54 people. Sampling based on the variables used is the implementation of family hope programs in improving the economy of the poor. The results showed that (1) the family program of hope in its implementation in Renggeang Village, Limboro Subdistrict, Polewali Mandar Regency went very well. This can be seen from the average score obtained from each question item of 224 or 82.6% which indicates that the implementation of the family hope program runs very well (2) The implementation of the family hope program in Renggeang Village, Limboro District, Polewali Mandar Regency can improve the economy of the poor. This can be seen from the average score obtained from each statement item of 257 or 90.7% which indicates that there is a true improvement in the economy of the poor.